Access to Support Services for Newcomer Youth Through the Process of School Integration: A Critical Narrative Literature Review. (December 2022) - Kalchos, Linnea F.; Kassan, Anusha; Ford, Laurie
While the numbers of newcomer youth continue to grow in Canada, few studies have sought to critically capture experiences of school integration and access to school-based psychosocial support services during their transition. Guided by a critical social justice lens, this research seeks to investigate issues of inequity due to the marginalization of newcomer youth in schools. The intent of this critical narrative review is to summarize, interpret, critique, and synthesize what is currently known about the ways newcomer youth access and experience school-based psychosocial support services (S-BPSS) throughout the process of school integration. This paper presents the critical narrative literature review process, a discussion of the themes that emerged from the review, and a discussion of the literature within the context of school integration. The following themes that underscore the experiences of newcomer youth accessing school-based psychosocial support services were identified: (a) underutilization/discrimination, (b) culture shift, (c) transition planning, and (d) lived experience. Important directions for future research, including the importance of studies that prioritize the perspectives of newcomer youth themselves and the implications of their lived experience for S-BPSS are provided.